Propuesta de rehabilitación de la Vía El Tigrillo aplicando el método PCI en el cantón Alfredo Baquerizo Moreno - Anchundia Fajardo, Danis Henrry (2024)
The PCI (Pavement Condition Index) method is a process that consists of determining the condition of the pavement through visual inspections, identifying the type of damage, severity and number of faults found. Introducing "deducted values" as an indication of the class, level of severity and amount that each damage has on the condition of the pavement, ranging from zero (poor condition) to one hundred (perfect condition). In the present work, the pavement condition (PCI) was obtained on the El Tigrillo road in the Alfredo Baquerizo Moreno Canton of the Province of Guayas, and the calculation of the TPDA was carried out. 15 samples were studied, observing that the asphalt pavement is in a state from BAD to UNACCEPTABLE, and it was identified that the most predominant faults found are: crocodile skin cracking and holes in 66.67%, and rutting in 33.33%.....